Microangiopathic Hemolytic Anemia Following Transjugular Intrahepatic Portosystemic Shunt Creation in an Adolescent - Khoo, Jing Y.; Lessne, Mark L.; Gopalareddy, Vani V. (ACG case reports journal, 2025)
ABSTRACTTransjugular intrahepatic portosystemic shunt (TIPS) creation is an effective approach to address the complications of portal hypertension. This case report describes an adolescent boy who underwent TIPS creation with an expanded polytetrafluorethylene-lined stent graft for portal hypertension secondary to sinusoidal obstruction syndrome. He subsequently developed microangiopathic hemolytic anemia, an uncommon complication of covered stents that is not well reported in the pediatric population. Despite its rarity and typical conservative management, microangiopathic hemolytic anemia should be considered and regularly monitored in the months following TIPS creation in pediatric patients.